2007
DOI: 10.1128/jvi.00780-07
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Neurological Disease in Scrapie-Infected Mice Induced for Experimental Autoimmune Encephalomyelitis

Abstract: During the years or decades of prion disease incubation, at-risk individuals are certain to encounter diverse pathological insults, such as viral and bacterial infections, autoimmune diseases, or inflammatory processes. Whether prion disease incubation time and clinical signs or otherwise the pathology of intercurrent diseases can be affected by the coinfection process is unknown. To investigate this possibility, mice infected with the scrapie agent at both high and low titers were subsequently induced for exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 40 publications
1
17
1
Order By: Relevance
“…30,31 Shortly, 6-to 8-week-old female C57BL/6 mice were immunized with an emulsion containing 200 μg of MOG (70% purified; synthesized at Hebrew University, Jerusalem, Israel) in saline and an equal volume of complete Freund's adjuvant containing 5 mg/mL H37RA (Difco Laboratories, Detroit, MI, USA). The inoculum (0.2 mL) was injected subcutaneously into right and left flanks.…”
Section: Induction Of Eaementioning
confidence: 99%
“…30,31 Shortly, 6-to 8-week-old female C57BL/6 mice were immunized with an emulsion containing 200 μg of MOG (70% purified; synthesized at Hebrew University, Jerusalem, Israel) in saline and an equal volume of complete Freund's adjuvant containing 5 mg/mL H37RA (Difco Laboratories, Detroit, MI, USA). The inoculum (0.2 mL) was injected subcutaneously into right and left flanks.…”
Section: Induction Of Eaementioning
confidence: 99%
“…In our previous work [20], we showed that mice may succumb to the co-induced scrapie-EAE disease at similar incubation times with very different levels of brain PrP Sc , those varying from undetectable levels to the high levels observed in mice with classical scrapie. To this effect, we next investigated whether mice succumbing to the co-induced disease generate a new prion strain that can transmit disease independent of PrP Sc inoculum levels, or whether disease transmission from these mice correlate with the accumulated PrP Sc levels when in brain homogenates.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the cells were extensively washed to remove excess nonspecific bound prions, extracted, and normalized for their protein content (see Materials and Methods). Samples were treated with PK and analyzed by Western blot with anti‐PrP mAb IPC1 (Friedman‐Levi et al, 2007) or, omitting the PK digestion step, with anti‐MVM capsid antibody. As depicted in Figure 1a, under these conditions, MVM‐infected cells incorporated significantly more exogenous PrP Sc than control cells.…”
Section: Resultsmentioning
confidence: 99%
“…For example, mastitis in scrapie‐infected sheep, presumably caused by the lentivirus Maedi‐Visna virus (MVV), resulted in deposition of PrP Sc in the inflamed mammary glands (Ligios et al, 2005), and preconditioning of various chronic follicular inflammations in mice induced deposition of PrP Sc and prion infectivity in the sites of infiltration (Heikenwalder et al, 2005). In a recent study, we showed that induction of CNS inflammation in the form of experimental autoimmune encephalomyelitis (EAE) in mice incubating prion disease resulted in early death from an exacerbated EAE‐like syndrome concomitant with deposition of PrP Sc in spinal cord white matter (Friedman‐Levi et al, 2007).…”
mentioning
confidence: 99%